Dampak Green Campaign pada Media Sosial Terhadap Purchase Intention Slow Fashion Product dengan Environmental Attitude sebagai Variabel Mediasi - Tania Adialita; Eka Septiarini (Universitas Batanghari, 2023)
According to a survey by the Ministry of Industry, in 2019, the export growth of the apparel textile industry in Indonesia increased significantly to 56% of creative economy exports. Fast-fashion products encourage consumers to dress continuously, following trends at low cost. The fact is that fast-fashion products harm both social and environmental aspects. However, slow-fashion products have a longer product life cycle, better quality, and relatively higher prices and require full awareness from fashion businesses and consumers to slow down the production and consumption cycles of fashion products. Slow-fashion businesses carry out campaigns through Instagram, hoping that consumers will become aware of environmental conditions, adopt green behaviour and change attitudes toward consuming slow-fashion products to preserve the environment. This research is expected to provide information to slow-fashion businesses regarding purchase intention and environmental attitudes from green campaigns through Instagram to support environment-based business activities, especially slow-fashion products from Indonesia. The quantitative research method is obtained from a Likert scale questionnaire survey and analyzed using Structural Equation Modeling. Using the convenience sampling method, 128 respondents found that green campaigns and environmental attitudes positively and significantly affect the purchase intention of slow-fashion products. Furthermore, environmental attitude is mediating variable between green campaigns and slow fashion product purchase intention